Annual plankton dynamics in an Antarctic saline lake - Bell, Elanor M.; Laybourn-Parry, J. (1999)
1. The plankton dynamics of Ace Lake, a saline, meromictic basin in the Vestfold Hills, eastern Antarctica was studied between December 1995 and February 1997. 2. The lake supported two distinct plankton communities; an aerobic microbial community in the upper oxygenated mixolimnion and an anaerobic microbial community in the lower anoxic monimolimnion. 3. Phytoplankton development was limited by nitrogen availability. Soluble reactive phosphorus was never limiting. Chlorophyll a concentrations in the mixolimnion ranged between 0.3 and 4.4 mu g L-1 during the study period and a deep chlorophyll maximum persisted throughout the year below the chemo/oxycline. 4. Bacterioplankton abundance showed considerable seasonal variation related to light and substrate availability. Autotrophic bacterial abundance ranged between 0.02 and 8.94 x 10(8) L-1 and heterotrophic bacterial abundance between 1.26 and 72.8 x 10(8) L-1 throughout the water column. 5. The mixolimnion phytoplankton was dominated by phytoflagellates, in particular Pyramimonas gelidicola. P. gelidicola remained active for most of the year by virtue of its mixotrophic behaviour. Photosynthetic dinoflagellates occurred during the austral summer, but the entire population encysted for the winter. 6. Two communities of heterotrophic flagellates were apparent; a community living in the upper monimolimnion and a community living in the aerobic mixolimnion. Both exhibited different seasonal dynamics. 7. The ciliate community was dominated by the autotroph Mesodinium rubrum. The abundance of M. rubrum peaked in summer. A proportion of the population encysted during winter. Only one other ciliate, Euplotes sp., occurred regularly. 8. Two species of Metazoa occurred in the mixolimnion; a calanoid copepod (Paralabidocera antarctica) and a rotifer (Notholca sp.). However, there was no evidence of grazing pressure on the microbial community. In common with most other Antarctic lakes, Ace Lake appears to be driven by 'bottom-up' forces.